Acclimation of Koliella antarctica to different light intensities - La Rocca N; Moro I; Sciuto K; Rascio N; Morosinotto T (Società Italiana di Biologia Vegetale (SIBV), 2013)
Data on the cultivation of Koliella antarctica at different light intensities are shown.